Kewenangan DPRD dalam Membahas dan Menindaklanjuti Laporan Pertanggungjawaban Walikota Bandar Lampung (Studi Pada Kota Bandar Lampung) - Budiyono (PRANATA HUKUM, 2014)
Based on the function of making laws, Parliament is authorized to make the Regulation on the implementation of this function can be used by right or right of initiative and the initiative amendment rights or the rights of the change. With the exercise of regulatory functions by Parliament, the governments policies in the region would better reflect the will of the people in the region. The authority of Parliament to discuss and follow up Bandar Lampung Mayor Accountability Report 2006-2010 period pursuant to Article 42 paragraph (1) letter (h) of Law No. 32 Year 2004 onÂ Regional Government. Article 17 paragraph (2), Article 23 of Government Regulation No. 3 Year 2007. The constraints in the discussion of Bandar Lampung Mayor accountability report lack of response from the community are delivered directly to the Government of Bandar Lampung on LPPD information that has been published. The absence of mechanisms / rules clear to the public complaints on the delivery of information LPPD, Discussion Regional Head accountability report in parliament tend subjectiv / politically so that the recommendations given Parliament the accountability report less objectiv Regional Head.